IMPACT OF NON-FINANCIAL REWARDS ON EMPLOYEES MOTIVATION IN BANKING SECTOR OF PESHAWAR, PAKISTAN - Uzair, Zakkia; Mehmood, Asim (The journal of contemporary issues in business and government, 2021)
This papershows to measure the impact of non-financial rewards on the motivation of employees in different banks of Pakistan. The purpose of this paper is to know the impact of the non-financial rewards on employee’s motivation andwill classify to what extent the HR are taking care of this source of employee motivation.The paper follows an empirical study and quantitative approach. For non-financial rewards, there are fiveindependent variables taken for this study; rewards & recognition, career opportunity, promotion, participation of employees in decision-making and responsibility to identify their impact on the employee’s motivation. For effective collection of primary data from the target respondents, a Likert scaled questionnaire used, and 185 employees are taken from seven different banks in, Peshawar Pakistan. SPSS used to evaluate all of the data in order to find and measure the spearman association among the dependent and independent variables. All the data presented using tables.All non-financial reward variables found to have a significant association in the analysis. HR managers in the banking industry may find this study useful. The paper offers a basis for understanding organizational motivation problems. It is a valuable contribution to the field of HR management expertise, as it examines the factors that influence employee motivation and offers solutions to challenges that workers face at work. The paper would also force the banks managers to consider the issues of employee motivation for the sake of the company's overall success.